Estimation of Tactile Discriminatory Fitness in Hands of Public Transport Drivers - Nepal, Ojashwi; Thapa, Samjhana; Kasti, Roshan; Jha, Reena Kumari; Amatya, Mrigendra (Journal of College of Medical Sciences-Nepal, 2020)
Background: Public transport drivers are constantly being exposed to stimuli and are at risk of disorder of peripheral nervous system which can be further complicated by comorbidities. Thus, we wanted to examine intactness of tactile discriminatory ability in healthy drivers by comparing it to healthy samples of non-driving population. Since two point discrimination (TPD) test is frequently used for neurological assessment of tactile stimulation we determined and compared various locations in hands of two populations. Methods: Participants were asked to answer whether they feel one point or two points touch by blunted end of simple compass divider in their hand. The minimum distance between the points at which the participants could answer correctly was noted as two point discrimination value. Results: Drivers had TPD range of 2-4mm with mean 2.53±0.62 and, 1-4mm with mean 2.6±0.72 at middle finger of right and left hand respectively. Following t-test between drivers versus students, significant difference in the mean TPD value in the proximal palm supplied by median nerve (p=0.016) and proximal palm corresponding to ulnar nerve (p=0.032) on the right hand was found. On the left hand, significant difference in the mean TPD value is found in the proximal palm corresponding to median nerve (p=0.008) and ulnar nerve (p=0.043) respectively. Conclusion: Healthy public transport drivers have less tactile discriminating prowess at proximal palmar surface of hand. Examined distal phalanges and distal palm showed no significant difference in mean of TPD values for healthy drivers versus students.